Designing a Model for Accountants’ Whistleblowing Against Financial Fraud - Rahimi, Mohammad; Janani, Mohammad Hasan; Sefaty, Farid; Ghiyasvand, Alireza (Business, Marketing, and Finance Open, 2025)
This study employs real data and information to develop a model for accountants' whistleblowing against financial fraud. From the perspective of its objective, this research can be classified as an applied study. The qualitative research population includes accounting faculty members, certified accountants, and official judicial experts. This study utilized a grounded theory approach, and after conducting 11 interviews, theoretical saturation was achieved. In the next phase, 18 hypotheses were formulated and distributed among 342 certified accountants. Structural equation modeling (SEM) techniques were employed to test the research hypotheses. The results indicated that financial corruption has a significant positive impact on social responsibility towards society and social norms. Whistleblowing positively and significantly affects social responsibility towards society and social norms. Organizational communication has a positive and significant effect on social responsibility towards society and social norms. Organizational security also exerts a positive and significant influence on social responsibility towards society and social norms. Attitudes have a significant positive effect on social responsibility towards society and social norms. Personality traits positively and significantly influence social responsibility towards society and social norms. Organizational support regulations have a significant positive impact on social responsibility towards society. The internal organizational environment positively and significantly affects social norms. Furthermore, social responsibility towards society has a positive and significant impact on professional ethical values and optimal reporting. Social norms also exert a positive and significant influence on professional ethical values and optimal reporting.